Batik Samudra Goes to School: Konservasi Ragam Hias Aceh Berbasis Projek di Sekolah - Mufti Riyani; Hanafiah, Hanafiah; Dian Kusumawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The low level of students' knowledge and understanding of their social and cultural environment, as well as their historical identity, necessitates a concerted and collaborative effort. One indicator of this limited knowledge and understanding of Aceh’s historical and cultural identity is the inadequate awareness among both teachers and students regarding their region’s decorative arts. In the partner schools, this is evident through the limited creativity displayed by teachers and students in producing the Projek Penguatan Profil Pelajar Pancasila (P5) with a local wisdom theme. Furthermore, schools face challenges in comprehending the steps required for P5 implementation, alongside difficulties in integrating technology within the project. This Community Service initiative aims to address these issues by integrating a conservation model of Acehnese decorative arts with the application of Batik Samudra technology in the P5 theme at SDN Alue Buloh, East Aceh Regency, aligning with the specific challenges faced by partner schools. The method used is training and mentoring The steps undertaken in this community service project adhere to the stages of P5 implementation within the school setting, which include: 1) Introduction or conceptualization, 2) Contextualization, 3) Action, and 4) Reflection. The outcomes of this initiative are not only the creation of Batik Samudra derivative products but also the enhancement of teachers' understanding and skills in P5 implementation. Additionally, there has been notable improvement in students' understanding and appreciation of Acehnese decorative motifs and batik as part of world cultural heritage. This Community Service has had an impact on the ability of partner schools to implement the Strengthening Pancasila Student Profile Project ideally, especially with the theme of local wisdom. The ability to identify and explore local decorative varieties is an indicator of P5's contextualization ability, while Sigeupah Buloh batik work is a skill and ability in the action and reflection stages.